Smart Feeding System Using IoT Sensors to Optimize Feed Conversion Ratio (FCR) and Growth Performance in Broiler Production - Mohamad Nasir (Livestock Science & Innovation Journal, 2025)
Background: Traditional feeding systems in broiler production often result in feed waste and suboptimal growth performance, affecting both profitability and sustainability. The integration of Internet of Things (IoT) technology in livestock management offers potential solutions for precision feeding.Objective: This study aims to evaluate the effectiveness of an IoT-based smart feeding system in optimizing Feed Conversion Ratio (FCR) and growth performance in broiler chickens compared to conventional feeding methods.Method: A total of 480-day-old Ross 308 broilers were allocated into two treatment groups: conventional feeding (CF, n=240) and IoT-based smart feeding (SF, n=240). The smart feeding system utilized load cell sensors, environmental sensors (temperature, humidity), and automated feeding algorithms. Data collection included daily feed intake, body weight, FCR, mortality rate, and production costs over a 35-day production cycle.Findings and Implications: The SF group demonstrated significantly better performance with FCR of 1.52±0.08 compared to CF group (1.78±0.12, P<0.01). Average daily gain increased by 14.3% (62.8±3.2 g/day vs 54.9±4.1 g/day, P<0.01). Feed waste reduced by 23.5%, and production costs decreased by 18.7% per kilogram of live weight. The system achieved 94.2% accuracy in feed demand prediction.Conclusion: IoT-based smart feeding systems significantly improve FCR, growth performance, and economic efficiency in broiler production, representing a valuable technology for sustainable poultry farming practices.